Sufi Dance in the Qur'an, Hadith, and Psychology: A Critical Reassessment of Spiritual Claims and Therapeutic Benefits - Muhammad Royyan Faqih Azhary; Edi Massolihin; Andi Mustopa; Joharis bin Asis; Muthohharun Afif (IJoIS: Indonesian Journal of Islamic Studies, 2026)
This study aims to critically analyze Sufi Dance, also known as Whirling Dervish, from three interdisciplinary perspectives: the Qur'an, Hadith, and Psychology. Existing studies lack an integrated critical analysis combining Qur'anic, hadith, and psychological perspectives. Using a qualitative library research method with a content analysis approach combined with sanad (chain of narrators) and matan (text) criticism, this research investigates the epistemic origins of Sufi Dance as a spiritual expression within Sufism, its claimed religious foundations, and its psychological impacts. The findings reveal a significant discrepancy between its spiritual claims and its empirical benefits. From the Qur'anic perspective, there is no direct or sound evidence supporting Sufi Dance as a prescribed form of worship, as the often-cited verse from QS. Sad: 33 is interpreted through a weak and overly liberal analogy. From the Hadith perspective, critical analysis of sanad and matan demonstrates that the narrations used to justify this practice are either weak (da'if) or forged (maudhu'), while authentic hadiths about expressions of joy are contextualized as permissible entertainment rather than established ritual worship. Conversely, from the psychological perspective, Sufi Dance shows substantial benefits as a form of spiritual psychotherapy, where structured movement combined with dhikr (remembrance of God) induces mental calmness and inner peace, and fosters positive behavioral changes such as increased patience, focus, and self-confidence. In conclusion, while Sufi Dance lacks valid foundations as ritual Islamic worship (ibadah mahdhah) from the primary sources of Sharia, it holds significant value as a cultural heritage and a psycho-spiritual discipline for mental well-being. This study recommends a clear distinction between its religious claims and its cultural-psychological utility to prevent theological confusion while appreciating its therapeutic role. The contributions of this research are twofold: first, a normative contribution through the application of hadith criticism to the practice of Sufi Dance, and second, an interdisciplinary contribution integrating Sharia and psychological perspectives.